Child Feeding Practices, Maternal Health and the Nutritional Status of Children Among Polygynous Families of the Matigsalug - D. ALFABETO, SEDD; S. VALMORIDA, JOSE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The study determined the child feeding practices and maternal health in relation to the nutritional status of children among polygynous families of Matigsalug Manobos in Sinuda, Kitaotao, Bukidnon. The respondents of the study were children aged two to eighteen years old and mothers aged fifteen to sixty years old. To assess the nutritional status of the respondents, the Body Mass Index (BMI) was used as a tool. Contrary to predictions, the study proved no significant association between maternal health and children's nutritional status. However, the type of food and frequency of feeding was positively associated with children's nutritional status with the type of-food having the strongest significance.